Contrast-enhanced ultrasound evaluation of primary renal squamous cell carcinoma: a case report - Jia, Yuhao; Zhang, Qunxia (Frontiers in Oncology, 2023)
Renal squamous cell carcinoma (RSCC) is very rare, and there are few reports about it so far. Here we report a unique case of renal squamous cell carcinoma examined by contrast-enhanced ultrasound(CEUS), which has never been reported before. In addition, the results of CEUS showed some unique features, different from other imaging examinations. The purpose of this case report is to clarify the CEUS findings of this case and analyze its potential value in early diagnosis of RSCC.